Survivability and release process of Lactobacillus plantarum SU-LS36 encapsulated with native and modified taro starch under simulated digestive conditions - Setiarto, R. Haryo Bimo; Harsi Dewantari Kusumaningrum,; Betty Sri Laksmi Jenie,; Tatik Khusniati,; Masrukhin,; Sulistiani, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research aimed to evaluate the viability, survivability, and release process of the encapsulated Lactobacillus plantarum SU-LS36 in the simulated gastric juice (SGJ), simulated intestinal juice (SIJ), and simulated colon juice (SCJ). We tested four types of encapsulations: native taro starch (NTS), modified taro starch (MTS) by heat moisture treatment (HMT), autoclaving-cooling-2 cycles (AC-2C), and maltodextrin (commercial encapsulant). We found that L. plantarum SU-LS36 with AC-2C-modified taro starch (MTS) showed the highest viability in SGJ (6.95 log CFU/g), SIJ (7.09 log CFU/g), and SCJ (7.85 log CFU/g) after incubation up to 4 h. AC-2C MTS dissolved or released more rapidly from its encapsulant material in the colon in SCJ than in NTS, HMT MTS, and maltodextrin. The longest time release of L. plantarum SU-LS36 encapsulated in AC-2C MTS was 3 h in SIJ conditions, 2 h in SGJ, and the fastest (1 h) in SCJ. The encapsulated L. plantarum SU-LS36 was released through a dissolution process (SGJ and SCJ) and by pancreatin activity (SIJ). Conclusively, AC-2C MTS could maintain the viability of L. plantarum SU-LS36 cells to the colon at 6.04 log CFU/g and fulfilled the minimum requirement of biovalue (MBV) probiotics set forth by the US FDA (6-7 log CFU/g).